Mussa Puzzle Redux - Itskhoki, Oleg; Mukhin, Dmitry (Econometrica, 2025)
The Mussa (1986) puzzle is the observation of a sharp and simultaneous increase in the volatility of both nominal and real exchange rates following the end of the Bretton Woods System of pegged exchange rates in 1973. It is commonly viewed as a central piece of evidence in favor of monetary non‐neutrality because it is an instance in which a change in the monetary regime caused a dramatic change in the equilibrium behavior of a real variable—the real exchange rate—and is often further interpreted as direct evidence in favor of models with nominal rigidities in price setting. This paper shows that the data do not support this latter conclusion because there was no simultaneous change in the properties of the other macro variables, nominal or real; an extended set of Mussa facts falsifies both conventional flexible‐price RBC models and sticky‐price New Keynesian models. We present a resolution to the broader Mussa puzzle based on a model of segmented financial market, in which the bulk of the nominal exchange rate risk is held by financial intermediaries and is not shared smoothly throughout the economy, emphasizing the importance of monetary transmission via the risk premium channel.